Development and validation of RP HPLC method for determination of metformin and sitagliptin in bulk and pharmaceutical dosage form - D., Kavitha; Sahoo, S K; P., Venkateswara Rao; M., Nagamani; Ch., Bhagyalaxmi (Journal of Applied Pharmaceutical Research, 2017)
A simple and rapid reversed phase-high performance liquid chromatographic method was developed for simultaneous determination of Metformin and Sitagliptin in Tablet Dosage form. The elution was done with a mobile phase of Water: Methanol (60:40) on Intersil-BDS C18 column (250 × 4.6 mm, 5 μm particle size). The wavelength detector was set at 258 nm. Retention times for Metformin and Sitagliptin were around 2.869 min, 3.942 min respectively. The reliability and analytical performance of the proposed HPLC procedure were statistically validated according to the respect of linearity, ranges, precision, accuracy, repeatability, reproducibility, detection and quantification limits. Linear ranges were established between 20-80 μg/mL for both the drug. The LOD and LOQ for Metformin were found to be 0.663, 1.92 and for Sitagliptin were found to be 0.405, 1.228 respectively. The described High Performance Liquid Chromatography method was successfully employed for the analysis of pharmaceutical formulations containing combined dosage form